EFISIENSI PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI PADI CIGELUIS DI SUBAK ANYAR SIDEMBUNUT KECAMATAN BANGLI KABUPATEN BANGLI - Sukerta, I Kadek Agus; Kardi, Cening; Yudiarini, Nyoman (Agrimeta: Jurnal Pertanian Berbasis Keseimbangan Ekosistem, 2018)
The purpose of this research is to know: (1) the influence of rice seed production factor, phonska fertilizer, organic fertilizer, urea fertilizer, and labor to cigeluis paddy farm production in Subak Anyar Sidembunut Bangli District Bangli, and (2) Efficiency of farm production factor usage Cigeluis rice in Subak Anyar Sidembunut Bangli District of Bangli.        This research is a survey research conducted in Subak Anyar Sidembunut Bangli District of Bangli District. This location is found by simple random sampling, while the determination of respondents using census method. The production function of this research is the production function of "Cobb-Douglass". Meanwhile, to know the efficiency of the use of the factors of production is done with the value of production with the price of production factors used.            The result of the research showed that: cigeluis rice seed production, phonska fertilizer, organic fertilizer, urea fertilizer and cigeluis rice labor significantly increased the production of cigelis paddy farming in Subak Anyar Sidembunut Bangli Subdistrict of Bangli Regency; (2) the use of production factor (rice seed , Phonska fertilizer, urea fertilizer, and labor in cassava rice iesatani in Subak Anyar Sidembunut Bangli District Bangli District Not yet efficient or still needs to be upgraded from average usage.